Practice of assessing the resources of fish in Peter the Great Bay by data of Danish seine catches - L. N. Kim; D. V. Izmyatinsky (Известия ТИНРО)
Marine biological resources are usually assessed by trawl surveys; methods of these surveys are well-developed. However, number of fish populations is too high to be completely assessed by scientific surveys, so the data of commercial fishery have to be used, too. Danish seine is preferable method of the Russian commercial fishery in the Japan Sea and some other areas of the Russian EEZ. Principal possibility of fish stocks accounting with Danish seine is tested earlier by specialists of Kamchatka Research Institute of Fisheries and Oceanography for the West Kamchatka where the parallel surveys by trawl and Danish seine were compared that showed similar results. Continuing these experiments, the data of Danish seine catches in Peter the Great Bay are compared with the data of trawl catches in the same area. In spite of differences in construction of the Danish seine and trawl, the fish resources assessments by these gears are similar in this area, too. Some differences are associated with the three times thicker layer caught by the Danish seine. Because of this reason, yellowfin sole Limanda aspera prevailed in the catches of Danish seine but other Pleuronectidae plaices were more numerous in the trawl catches, obviously because of their aggregation closer to  the bottom.